Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XXI: New reports from Fujian Province - Zhang, Qianwen; Pang, Siyu; Bian, Xun (Zootaxa, 2023)
In this study, we describe and illustrate two new species and the female of Metriogryllacris (Metriogryllacris) obscurata Zhang, Pang & Bian, 2022 based on the specimens from Fujian Province. The new erected Homogryllacris foveolis sp. nov. (Chinese name: 凹板同蟋螽) is very similar to Homogryllacris rufovaria Liu, 2007 in appearance, but the two can distinguished by the spines of male tenth abdominal tergite and shapes of male subgenital plate. All the specimens are deposited in Guangxi Normal University.